ANALISIS PENGARUH STRUKTUR BIAYA DAN VOLUME PENJUALAN TERHADAP LABA PERUSAHAAN TERBUKA (TBK) - Tati Sulastri; Purwanti, Purwanti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to analyze the effect of cost structure and sales volume on the profit of a public company (TBK). The cost structure consisting of fixed costs and variable costs has a significant impact on the company's ability to achieve profit. Fixed costs, which do not change with fluctuations in sales volume, function as a fixed burden that must be borne by the company, so that the higher the fixed costs, the greater the sales volume needed to reach the break-even point. On the other hand, variable costs that are directly related to sales volume can be controlled by increasing production efficiency and resource management. In addition, high sales volume will help the company cover fixed costs faster and increase profits. This study uses a descriptive and quantitative analysis approach to examine the relationship between cost structure, sales volume, and profit of a public company. The results of the analysis show that efficient management of the cost structure, both fixed costs and variable costs, as well as an optimal increase in sales volume, can increase the company's profit. The interaction between these two factors, namely fixed costs and variable costs, together with sales volume, plays an important role in determining the profitability of a public company. This study provides insight for company managers in formulating appropriate cost management strategies, as well as the importance of monitoring sales volume effectively to achieve maximum profit. On the other hand, less than optimal management costs or a decrease in sales volume can have a negative impact on the company's profit.